Cross-cultural communication of medical knowledge in 19th century China: A corpus-based perspective through grammatical metaphor - Fan, Rui; Fang, Alex (Meta, 2025)
This study explores shifts in discourse strategies in the cross-cultural communication of medical knowledge from Britain to China in the 19th century. The study adopts a novel perspective via grammatical metaphor that encodes the cognitive construal of medical knowledge. A parallel corpus was constructed containing both the original text in English and the translated text in Chinese. Extensive linguistic annotation of the corpus was carried out to identify metaphor-congruency shifts encoded grammatically as noun-to-verb and noun-to-adjective shifts between the source language and the target language. Based on empirical observations, the study uncovers important differences in communication strategies across the two texts through metaphor-congruency changes as a meaning-making choice for knowledge construal. To us, such shifts in the semiotic representation as communication strategies might represent cultural adaptations necessary for the smooth transmission of disciplinary knowledge across British and Chinese cultures. The study suggests that the cognitive underpinning of linguistic encodings is specific to explicitation and local experience, which influence how ideas and concepts are perceived and represented in medical discourse in particular and cross-cultural communication in general.